La dissimulation qui apparaît - Radvánszky, Anikó (Verbum – Analecta Neolatina, 2012)
Blanchot got closest to seizing the self-reflexivity of the literary work of art in the third piece of the triptych of Èze, a short story entitled Celui qui ne m’accompagnait pas. The central plot of the story is woven around a conversation the narrator is involved in with a mysterious "he", who is the other, unknown part of himself and an anthropomorphic work of art at the same time. The scene of the story gradually becomes an imaginary one, "the literary space" itself, making a possible entrance into the void, the lack of time, where the writingmay be born.